PENGUKURAN KUALITAS JARINGAN INTERNET DENGAN SINYAL 4G LTE OPERATOR TELKOMSEL DI KOTA MEDAN DENGAN METODE QUALITY OF SERVICE (QoS) - Yussa Ananda (Jurnal Simetri Rekayasa, 2021)
Today's internet needs in information communication are growing, internet networks are getting wider such as 1G, 2G, 3G and 4G technologies. Long Term Evolution (LTE) is a long term evolution radio access network issued by 3rd (Generation Partnership Project). To find out internet network services around the Jln. Imam Bonjol, Medan City, has carried out tests and measurements with the final result obtained an average QoS index of 3.2 with a satisfactory category, namely by using the Quality Of Service (QoS) method for the quality and power of data transfer. The Quality Of Service (QoS) method contained in a TCP/IP network is one that focuses on the allocation of bandwidth in the internet network that flows fairly, as needed. QoS parameters that rely on the testing process on throughput, delay time, latency time and packet request time